2017
DOI: 10.2527/jas.2017.1377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding pregnant beef cows selenium-enriched alfalfa hay on selenium status and antibody titers in their newborn calves

Abstract: In newborn dairy calves, it has been demonstrated that supranutritional maternal and colostral Se supplementation using Se yeast or sodium selenite, respectively, improves passive transfer of IgG. In beef cattle, agronomic biofortification with Se is a more practical alternative for Se supplementation, whereby the Se concentration of hay is increased through the use of Se-containing fertilizer amendments. It has been previously demonstrated that agronomic Se biofortification is an effective strategy to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…As previously reported [20], fertilizing fields with increasing amounts of Na-selenate increased the Se concentration of third-cutting alfalfa hay from 0.34 mg Se/kg DM (non-fertilized control) to 2.42 and 5.17 mg Se/kg DM for Na-selenate application rates of 45.0 and 89.9 g Se/ha, respectively. Calculated Se intake from dietary sources was 8.3 (including 3 mg Se/head daily from Na-selenite), 27.6, and 57.5 mg Se/ head daily for cows consuming 70% alfalfa hay and 30% grass hay with Se concentrations of 0.34 to 2.42 and 5.17 mg Se/kg in the alfalfa hay DM, respectively.…”
Section: Fertilizing With Sodium Selenate Increases Selenium Content supporting
confidence: 84%
See 4 more Smart Citations
“…As previously reported [20], fertilizing fields with increasing amounts of Na-selenate increased the Se concentration of third-cutting alfalfa hay from 0.34 mg Se/kg DM (non-fertilized control) to 2.42 and 5.17 mg Se/kg DM for Na-selenate application rates of 45.0 and 89.9 g Se/ha, respectively. Calculated Se intake from dietary sources was 8.3 (including 3 mg Se/head daily from Na-selenite), 27.6, and 57.5 mg Se/ head daily for cows consuming 70% alfalfa hay and 30% grass hay with Se concentrations of 0.34 to 2.42 and 5.17 mg Se/kg in the alfalfa hay DM, respectively.…”
Section: Fertilizing With Sodium Selenate Increases Selenium Content supporting
confidence: 84%
“…We previously reported that concentrations of IgG1 in colostrum increased in a linear relationship to the amount of Se ingested by the dam [20]. The mechanism by which High-Se supplementation increases colostral IgG1 concentration is unknown, and multiple factors may be involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations